2023
DOI: 10.1101/2023.04.11.535169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histone demethylase KDM5 regulates cardiomyocyte maturation by promoting fatty acid oxidation, oxidative phosphorylation, and myofibrillar organization

Abstract: Rationale: Human pluripotent stem cell-derived CMs (iPSC-CMs) are a valuable tool for disease modeling, cell therapy and to reconstruct the CM maturation process and identify, characterize factors that regulate maturation. The transition from immature fetal to adult CM entails coordinated regulation of the mature gene programming, which is characterized by the induction of myofilament and OXPHOS gene expression among others. Recent studies in Drosophila, C. elegans, and C2C12 myoblast cell lines have implicate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Recently, a study published in Exp Mol Med suggested that inhibiting KDM5A could ameliorate pathological cardiac fibrosis ( 37 ). However, another study submitted to BioRxiv ( 38 Preprint ) suggests KDM5A could regulate cardiomyocyte maturation by promoting fatty acid oxidation, oxidative phosphorylation, and myofibrillar organization. Those studies indicate a complex role for KDM5 in regulating cardiomyocyte cell fate decision and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study published in Exp Mol Med suggested that inhibiting KDM5A could ameliorate pathological cardiac fibrosis ( 37 ). However, another study submitted to BioRxiv ( 38 Preprint ) suggests KDM5A could regulate cardiomyocyte maturation by promoting fatty acid oxidation, oxidative phosphorylation, and myofibrillar organization. Those studies indicate a complex role for KDM5 in regulating cardiomyocyte cell fate decision and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…This difference can be attributed to the non-cell autonomous effects leading to lipotoxicity [5] as proposed by Li et al [3] . Furthermore, in another study by Ghosh et al [6] , skeletal muscle-specific deletion of CPT1B resulted in reduced α-KG, contrary to a substantial increase in α-KG as seen by Li et al [3] . Therefore, to unequivocally rule out any deleterious effects in CM specific Cpt1b knockout mice, a long-term cardiac function and survival analysis is warranted.…”
mentioning
confidence: 86%
“…Therefore, to unequivocally rule out any deleterious effects in CM specific Cpt1b knockout mice, a long-term cardiac function and survival analysis is warranted. Recent studies have documented the role of the KDM5 family of proteins in the maturation of cardiac myocytes [ 7 ] . It was shown that the levels of KDM5 gradually decrease during the maturation of CM and are negligible in the mature adult CM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study demonstrated that inhibiting KDM5 in induced pluripotent stem cell derived cardiomyocytes promotes their maturity. This maturation program is facilitated by the KDM5 s through the regulation of sarcomeric and OXPHOS genes [32 ▪▪ ]. KDM5 s thus epigenetically regulate the developmental gene program by suppressing maturation and promoting fetal gene expression.…”
Section: Introductionmentioning
confidence: 99%